Developmentally regulated cell death on expression of the fungal avirulence gene Avr9 in tomato seedlings carrying the disease-resistance gene Cf-9. - Hammond-Kosack, K E (1994)
Plant defense responses are induced when the products of disease-resistance genes and pathogen avirulence genes interact. We report here the effects of expressing the Cladosporium fulvum avirulence Avr9 gene product in a tomato line containing the Cf-9 disease-resistance gene. A synthetic Avr9 gene was constructed to produce constitutive high-level expression of AVR9 peptide in the plant apoplast. Avr9 expression in Cf-9-containing tomato lines is lethal, but cell death is developmentally regulated, in that necrosis is not visible until 10 days after planting seed. Plant lines lacking Cf-9 and expressing Avr9 remain healthy. The synthetic Avr9 gene exhibited the same specificity of action as the authentic C. fulvum Avr9 gene. Our results have significant implications for strategies using the gene combination Avr9/Cf-9 to engineer plants with enhanced disease resistance.